IL-23/IL-17 INHIBITORS IN IMMUNOINFLAMMATORY RHEUMATIC DISEASES: NEW HORIZONS - E. L. Nasonov; T. V. Korotaeva; T. V. Dubinina; A. M. Lila (Научно-практическая ревматология)
Recently, more attention has been given to Th17 cells, the pathological activation of which plays a leading role in the development of a wide spectrum of human immunoinflammatory diseases (IID), including rheumatoid arthritis, psoriasis, ankylosing spondylitis, psoriatic arthritis, inflammatory bowel diseases, etc. This has served as an incentive to design new biological agents and small molecules, the main mechanism of action of which is based on blocking the pathological effects of interleukin-17 (IL-17), others are associated with the activation of Th17 cells cytokines or signaling pathways that regulate the effects of these cytokines. The review discusses current ideas about the mechanisms regulating the formation and functional activity of IL-17 family cytokines, as well as evidence for the importance of these cytokines in the pathogenesis of IID.